Thyroglossal duct carcinoma: report of a case - Pezzolla, Angela; Paradies, Daniele; Lattarulo, Serafina; Borraccia, Vittoria Fausta Daniela; Spinelli, Stefano; Ciampolillo, Anna; Madami, Luigi (European Journal of Oncology and Environmental Health, 2016)
Aim: Thyroglossal duct carcinoma (TDCa) is a rare malignant tumor arising within a thyroglossal duct remnant (TDR) or a thyroglossal duct cyst (TDC). Controversies exist regarding its origin: whether it represents a metastatic lesion of a primary thyroid cancer or a “de novo” origin. Patients and methods: Man with a visible and palpable subhyoid mass. Preoperative ultrasound scan and US-guided fine-needle aspiration cytology revealed suspicious papillary carcinoma in the TDC and thyroid nodules. Surgery consisted in removal of the hyoid bone and total thyroidectomy. Results: Histopathologic examination revealed papillary TDCa and a focus of papillary var. follicular microcarcinoma in the thyroid gland. Conclusions: Ultrasound scan with fine-needle aspiration cytology is beneficial in the preoperative diagnosis of carcinoma in TDC. Surgery is an adequate treatment for TDCa and the prognosis for TDCa is excellent. Adjuvant radioactive iodine and post-operative L-thiroxine suppressive therapy are appropriate in these cases. Our experience confirms the controversies about the origin of TDCa.